ChemInform Abstract: Surface Modification of Silicon Anodes for Durable and High—Energy Lithium‐Ion Batteries. Issue 28 (July 2015) - Son, Seoung‐Bum; Kappes, Branden; Ban, Chunmei
Abstract Review: [95 refs.